Fatty Acid Profile of Milk of Various Indigenous Cattle Breeds in Hot-Arid Region of Rajasthan (Indian Journal of Animal Production and Management, 2024)
The bioactive components refer to  compounds either naturally existing in food or  introduced during food processing that may have  physiological and biochemical functions when  consumed by humans and have crucial impacts on  human metabolism and beneficial effects on human  health, that guard neonates and adults against  pathogens and illnesses and Antioxidants may  positively affect human health by protecting the  body against damage caused by reactive oxygen  species, which attack membrane lipids, protein and  DNA. Bioactive components encompass proteins,  peptides, carbohydrates, lipids, glycolipids and  other minor biomolecules i.e. vitamins, lactoferrin,  enzymes, immunoglobulin and growth factors. The  present study was conducted on fatty acids in milk  of various indigenous cattle breeds viz. Kankrej,  Sahiwal and Rathi. For fatty acids, 36 milk samples  (12 from each breed) were collected from different  Livestock Research Station, Bikaner. Fatty acids  were measured by GC-MS. The analysis of  variance revealed monounsaturated fatty acids and  Poly unsaturated fatty acids significantly differed in  different indigenous cattle breeds whereas  saturated fatty acids did not differ. The present  study concluded that the milk from the indigenous  cattle breeds viz. Kankrej, Sahiwal, and Rathi have  distinct compositions and quantities of different  active components which can be harnessed for the  promotion of different functional foods based on  indigenous cattle milk and further pharmaceutical  preparations can be promoted for the benefit of  farmers and entrepreneurs.
Keywords: fatty acids; indigenous cattle; monounsaturated fatty acids; polyunsaturated fatty acids; saturated fatty acids